High-throughput system-wide engineering and screening for microbial biotechnology. (August 2017) - Vervoort, Yannick; Linares, Alicia Gutiérrez; Roncoroni, Miguel; Liu, Chengxun; Steensels, Jan; Verstrepen, Kevin J
Graphical abstract: Highlights: MAGE and CRISPR/Cas systems are increasingly used for large-scale genome engineering. Population based omics tools are optimized for higher throughputs but lack single cell resolution. Nanoliter-scale capsule or droplet reactors can be used for high-throughput single cell screening. Microchips allow ultra-high throughput picoliter-scale single cell phenotyping. Abstract : Genetic engineering and screening of large number of cells or populations is a crucial bottleneck in today's systems biology and applied (micro)biology. Instead of using standard methods in bottles, flasks or 96-well plates, scientists are increasingly relying on high-throughput strategies that miniaturize their experiments to the nanoliter and picoliter scale and the single-cell level. In this review, we summarize different high-throughput system-wide genome engineering and screening strategies for microbes. More specifically, we will emphasize the use of multiplex automated genome evolution (MAGE) and CRISPR/Cas systems for high-throughput genome engineering and the application of (lab-on-chip) nanoreactors for high-throughput single-cell or population screening.